2012
DOI: 10.3390/md10112481
|View full text |Cite
|
Sign up to set email alerts
|

Cultivable Alginate Lyase-Excreting Bacteria Associated with the Arctic Brown Alga Laminaria

Abstract: Although some alginate lyases have been isolated from marine bacteria, alginate lyases-excreting bacteria from the Arctic alga have not yet been investigated. Here, the diversity of the bacteria associated with the brown alga Laminaria from the Arctic Ocean was investigated for the first time. Sixty five strains belonging to nine genera were recovered from six Laminaria samples, in which Psychrobacter (33/65), Psychromonas (10/65) and Polaribacter (8/65) were the predominant groups. Moreover, 21 alginate lyase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 22 publications
2
33
0
Order By: Relevance
“…The polysaccharide alginate is found in brown alga cell walls, and alginate lyase excreting Polaribacter have been described before as abundant members of epiphytic bacterial communities on Laminaria sp. brown alga (Dong et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polysaccharide alginate is found in brown alga cell walls, and alginate lyase excreting Polaribacter have been described before as abundant members of epiphytic bacterial communities on Laminaria sp. brown alga (Dong et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This view is supported by high Flavobacteriia abundances in nutrient-rich habitats, such as aggregates of particulate organic matter (Williams et al, 2013) or in the microbiota of marine algae and invertebrates (Di Camillo et al, 2012;Dong et al, 2012). Also, so far sequenced genomes of marine Flavobacteriia have revealed clear adaptations towards biopolymer degradation (for example, Bauer et al, 2006;González et al, 2008;Woyke et al, 2009;Mann et al, 2013), as they feature high proportions of peptidase and glycoside hydrolase (GH) genes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 21 alginate lyase-excreting strains were isolated from the surface of the Arctic Laminaria and some cold-adapted alginate lyases were identified (Dong et al 2012). More recently, Martin et al (2015) isolated and identified 14 alginate lyase-excreting strains associated with the brown alga Ascophyllum nodosum , including one novel strain of Marinomonas.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [108] reported for the first time that the extracellular alginate lyase-like protein from Pseudomonas fluorescens exhibits high degradation activity for alginate. Dong and other scientists performed a study on bacteria isolated from the Arctic marine seaweed that produces alginate lyase [109]. In total, 65 bacterial strains were isolated from the kelp specimen, 21 of which exhibited alginate lyase activity.…”
Section: Alginate Lyasementioning
confidence: 99%
“…In total, 65 bacterial strains were isolated from the kelp specimen, 21 of which exhibited alginate lyase activity. Among these isolates, 11 bacterial strains exhibited an optimum temperature between 20 °C and 30 °C, which indicates that the extracellular lyases are cryophilic enzymes [109]. Moreover, the bacterial strains Psychrobacter , Winogradskyella , Psychromonas and Polaribacter produce alginate lyase.…”
Section: Alginate Lyasementioning
confidence: 99%